ANALISIS SPASIAL RISIKO BENCANA GEMPA BUMI DI KOTA PALU, SULAWESI TENGAH - Ardika Wibowo, Hilman
7.4 Magnitude earthquake that happened in Palu City, Central Sulawesi at 2018 causes massive losses and deaths. Based on “Laporan Situasi Gempa Bumi Sulawesi Tengah”, published by BNPB at 05 February 2019, the earthquake causes around Rp. 2,89 trillion material losses, around Rp. 15,58 trillion environmental damage, and 3.689 deaths. Disaster mitigation is needed for reducing the losses and deaths in upcoming earthquakes. Risk analysis can be executed for earthquake disaster mitigation. Using geographic information system and spatial analysis, earthquake risk level can be modeled. In this research, the risk level determined by multiplying earthquake hazard that represented by peak ground acceleration with the vulnerability and capacity of buildings. The result of building damage risk level modeling is validated by the real damage data after Palu Earthquake at 2018. As the result, there are 1.488 buildings fairly damaged, 68.873 buildings hardly damaged, and 46.093 buildings destroyed. The validation result shows that the modelling has 56.62% overall accuracy and 0.120 Kappa coefficient.